MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DALAM MENENTUKAN KALIMAT UTAMA MENGGUNAKAN MODEL PBL, NHT DAN SNOWBALL THROWING - Elisa, Herni Noor; Mahmuddin, Mahmuddin (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2025)
The limitation of students' critical thinking skills in Indonesian learning is a problem in this study. Students fail to solve problems, make decisions, and understand the text being read. Implementing Problem Based Learning (PBL), Number Head Together (NHT) Combination, and Snowball Throwing is an attempt to address this problem. The purpose of this study is to improve the critical thinking skills of students in grade 4 of SDN Berangas Timur 1, which consists of 25 students. This research was conducted in 3 meetings. Data were analyzed using descriptive techniques. The results of observation of teacher activities, student activities, critical thinking skills, and student learning outcomes are presented in the form of tables and graphs. Each indicator shows the success of teacher activities, student activities, critical thinking skills, and the achievement of individual and classical student learning completeness. The results showed that teachers' activities improved, with a score of 31 for the "Excellent" category and 84% for the "Very Active" category. Students showed an increase in critical thinking skills by 84% in the "Skilled" category and 92% in classical completeness. The results of this study show that the Problem Based Learning (PBL) model, the combination of Number Head Together (NHT), and Snowball Throwing can help improve critical thinking skills. Therefore, school principals, teachers, and subsequent researchers can use this information to improve their critical thinking skills. ABSTRAKKeterbatasan keterampilan berpikir kritis siswa dalam pembelajaran Bahasa Indonesia adalah masalah dalam penelitian ini. Siswa gagal memecahkan masalah, membuat keputusan, dan memahami teks yang dibaca. Menerapkan Problem Based Learning (PBL), Kombinasi Number Head Together (NHT), dan Snowball Throwing adalah upaya untuk mengatasi masalah ini. Tujuan penelitian ini adalah untuk meningkatkan keterampilan berpikir kritis siswa di kelas 4 SDN Berangas Timur 1, yang terdiri dari 25 siswa. Penelitian ini dilakukan dalam 3 pertemuan. Data dianalisis dengan menggunakan teknik deskriptif. Hasil observasi aktivitas guru, aktivitas siswa, keterampilan berpikir kritis, dan hasil belajar siswa disajikan dalam bentuk tabel dan grafik. Setiap indikator menunjukkan keberhasilan aktivitas guru, aktivitas siswa, keterampilan berpikir kritis, dan tercapainya ketuntasan belajar siswa secara individual dan klasik. Hasil penelitian menunjukkan bahwa aktivitas guru menjadi lebih baik, dengan skor 31 untuk kategori "Sangat Baik" dan 84% untuk kategori "Sangat Aktif". Siswa menunjukkan peningkatan keterampilan berpikir kritis sebesar 84% dalam kategori "Terampil" dan 92% dalam ketuntasan klasikal. Hasil penelitian ini menunjukkan bahwa model Problem Based Learning (PBL), kombinasi Number Head Together (NHT), dan Snowball Throwing dapat membantu meningkatkan keterampilan berpikir kritis. Oleh karena itu, kepala sekolah, guru, dan peneliti berikutnya dapat menggunakan informasi ini untuk meningkatkan keterampilan berpikir kritis mereka.